Bacterial Responses and Genome Instability Induced by Subinhibitory Concentrations of Antibiotics - Arnaud Gutierrez; Ivan Matic; Luisa Laureti (MDPI AG, 2013)
Nowadays, the emergence and spread of antibiotic resistance have become an utmost medical and economical problem. It has also become evident that subinhibitory concentrations of antibiotics, which pollute all kind of terrestrial and aquatic environments, have a non-negligible effect on the evolution of antibiotic resistance in bacterial populations. Subinhibitory concentrations of antibiotics have a strong effect on mutation rates, horizontal gene transfer and biofilm formation, which may all contribute to the emergence and spread of antibiotic resistance. Therefore, the molecular mechanisms and the evolutionary pressures shaping the bacterial responses to subinhibitory concentrations of antibiotics merit to be extensively studied. Such knowledge is valuable for the development of strategies to increase the efficacy of antibiotic treatments and to extend the lifetime of antibiotics used in therapy by slowing down the emergence of antibiotic resistance.